Functional assessment of DNA extraction methods from frozen human blood samples for Sanger sequencing analysis: Modified DNA extraction for Sanger sequencing - Vidyadharan, Pravi; CKV, Santhi; Sethumadhavan, Anjali; Gopala, Srinivas; T Raghavan, Cibin; Urulangodi, Madhusoodanan (Cellular and Molecular Biology, 2023)
The quality of input DNA is crucial for obtaining significant inferences from molecular techniques like Sanger sequencing and Next Generation Sequencing experiments. Many of the extraction methods are suitable for retrieving quality DNA from fresh blood and tissue samples, regardless of the isolation principle. However, while isolating DNA from frozen blood samples, processed tissue samples or low-quality samples, careful selection of suitable extraction methods is extremely important. Moreover, there is no standard protocol recommended for genomic DNA extraction from stored blood samples, particularly those stored in a Biobank, for applications like Sanger sequencing. Consequently, we have systematically compared different commercial DNA isolation kits with a modified manual extraction method for blood samples frozen for up to three years and assessed their quality, yield and suitability for PCR, Real-Time PCR and Sanger sequencing. The manual DNA extraction method was improved by incorporating a few modifications: a lower NaCl concentration was used for precipitating DNA and excluded the use of phenol. The modified method provided the maximum DNA yield from stored blood. Although all the methods tested were suitable for recovering DNA from stored blood, the modified method described here may be preferred for large-scale applications as it provides cost-effective ways to obtain large quantities of quality DNA. Most importantly, the DNA isolated by the modified method appears to be more stable in long-term storage at -80°C.